Comparative evaluation of nutritional compositions, antioxidant capacities, and phenolic compounds of red and green sessile joyweed (Alternanthera sessilis) - Othman, Azizah; Ismail, Amin; Hassan, Fouad Abdulrahman; Md Yusof, Barakatun Nisak; Khatib, Alfi (Elsevier Science BV, 2016)
Thenutritionalcompositions,antioxidantcapacities,andphenoliccompoundsof Alternanthera sessilis red (ASR) and green (ASG) in water and ethanolic extracts were compared. Nutritional compositions were determined according to anAOAC method.Total phenolic content was evaluated by a colorimetric reduction using the Folin–Ciocalteu method. Highperformance liquid chromatography combined with diode array and electrospray ionization mass spectrometric detection was used to the study phenolic compounds.Antioxidant capacities were evaluated by ﬁve different methods.The results showed that ASR contained signiﬁcantly (p < 0.05) higher protein, fat, carbohydrate and mineral contents compared to ASG. The ethanolic extracts of both ASR and ASG presented signiﬁcantly greater antioxidantcapacitythanthewaterextractsat p<0.05.Thetotalphenoliccontentexhibitedapositive correlation with the antioxidant capacities, which could be one of the critical contributors to the antioxidant activity of ASR and ASG.